Examining the Impact of Self Efficacy, Digital Literacy,and Social Support on Work Readiness among FKIP Students - Kurniawaty Fitri; Rosi Junita; Ahmad Rifqi (AMAR (Andalas Management Review), 2026)
This study examines the influence of self-efficacy, digital literacy, and social support on work readiness among students of the Faculty of Teacher Training and Education (FKIP). A quantitative research design was employed, with data collected through structured questionnaires administered to FKIP students. The data were analyzed using multiple linear regression analysis. The results indicate that self-efficacy, digital literacy, and social support each have a positive and statistically significant effect on students’ work readiness. Among the predictors, self-efficacy emerges as the most dominant factor, followed by digital literacy, while social support shows a smaller yet meaningful contribution. These findings suggest that FKIP students’ readiness to enter the teaching profession is shaped by a combination of internal psychological resources, digital competencies, and supportive social environments. The study underscores the importance of strengthening self-efficacy, integrating digital literacy into teacher education curricula, and providing structured academic support to enhance the professional readiness of prospective teachers.